Rapid Sintering and Synthesis of Nanostuctured FeCrAlSi-Al2O3 Composite by High-Frequency Induction Heating - Du, Song-Lee; Cho, Sung-Hun; Ko, In-Yong; Doh, Jung-Mann; Yoon, Jin-Kook; Park, Sang-Whan; Shon, In-Jin (KOREAN INST METALS MATERIALS, 2011)
Nanopowder of Fe2O3, Al, Cr and Si was fabricated by high energy ball milling. A dense nanostuctured. A(2)O(3) and 6.06Fe(0.33)Cr(0.16)Al(0.23)Si(0.29) composite was simultaneously synthesized and consolidated using high frequency induction heated sintering method within 1 minute from mechanically activated powders of Fe2O3, Al, Cr and Si. The grain sizes of Al2O3 and Fe0.33Cr0.16Al0.23Si0.29 in composite are 80 and 18 nm, respectively.
Keywords: MECHANICAL-PROPERTIES; TUNGSTEN CARBIDE; ALLOY; CONSOLIDATION; POWDERS